Land Use and selected Physical Geographical characteristics in the Lovrenc na Pohorju Municipality Area - Kop, Boštjan (Journal for Geography, 2014)
The article treats land use and selected physical geographical characteristic in the municipality of Lovrenc na Pohorju area. Selected physical geographical characteristics were statistically analysed and presented cartographically in GIS environment. The connection between characteristics was also analysed, as well as their impact on land use. Methodology of gathering data and statistical analysis is presented. Relief is with surface height, surface slope and surface aspect the main physical geographical factor of land use and the shape of cultural landscape.